APLIKASI BIOAKTIVATOR EM-4 DAN BOISCA DALAM PEMBUATAN PUPUK ORGANIK CAIR SEBAGAI PENGEMBANGAN LEMBAR KERJA MAHASISWA (LKM) BIOTEKNOLOGI LINGKUNGAN - Safitri, Wulan Indri Safitri Indri; Marhadi, Imam Mahadi; Wulandari, Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrack:The research was conducted to determine the effect of bio-activator EM-4 and Boisca in the manufacture of liquid organic fertilizer. This research was conducted from March to June 2015. The results are used for the development of LKM (StudentsWorksheet ) on the concept of environmental biotechnology. This study consisted of two phases: the manufacture of Liquid Organic Fertilizer and stage of development of LKM. Phase manufacture of Liquid Organic Fertilizer use research "True-Experimental Research" with completely randomized design (RAL), which consists of 4 treatments and 3 replications. While LKM refers to the development stage of research approaches Research and Development (R & D) by using ADDIE models developed from the research of liquid organic fertilizer. Parameters of this study is ratio C / N, Elements N, P and K, temperature and pH. The data obtained and analyzed statistically using analysis of variance. If significantly different continued with Duncan Multiple Range Test (DMRT) at significance level of 5%. LKM development while data obtained from the validation sheet is validated by 3 validator and analyzed descriptively. The results showed that the application of bio-activator EM-4 and Boisca affect the outcome of liquid organic fertilizer where the best treatment being owned by a treatment with a combination of EM-4 and Boisca. Results of the study was developed as LKM (StudentsWorksheet) is the composting material on the concept of environmental biotechnology. LKM were developed to obtain a valid category so that LKM can be used in the manufacture of compost material. Keywords: Bioactivator, liquid organic fertilizer, LKM, environmental biotechnology